Assessment of Surface Water Quality in the Krynka River Basin Using Fluorescence Spectroscopy Methods - Sergey Chufitskiy; Sergey Romanchuk; Besarion Meskhi; Anastasiya Olshevskaya; Victoria Shevchenko; Mary Odabashyan; Svetlana Teplyakova; Anna Vershinina; Dmitry Savenkov (Plants)
This study presents a biomonitoring study of surface waters in the Krynka River basin, encompassing three major regional reservoirs: Khanzhenkovskoe, Olkhovskoe, and Zuyevskoe. These water bodies face significant anthropogenic pressure from mining effluents, industrial discharges, and domestic wastewater. Key pollutants identified are surfactants (SAAs), sulfates, phenols, chlorides, and manganese, with chemical oxygen demand (COD) exceeding regulatory limits. The research was conducted in September 2024. Based on the Specific Combinatorial Water Pollution Index, surface waters in the studied objects can be characterized as slightly polluted. To assess the negative impact of the identified pollutants on hydrobionts, the species composition of phytoplankton of the studied water bodies was analyzed. In the Olkhovskoe Reservoir and Olkhovaya River, cyanobacterial blooms (Oscillatoria agardhii G.) were observed, altering biodiversity in the Krynka River and Zuyevskoe Reservoir. Phytoplankton genera Synedra, Amphiprora, and Navicula—established bioindicators of aquatic ecosystem health—were dominant in Khanzhenkovskoe Reservoir, signaling nutrient enrichment and organic pollution. Changes in the species composition and structure of phytoplankton in the Krynka River, its tributaries and reservoirs, indicate a change in the level of saprobic water bodies from β to α-mesosaprobic, which indicates both the general level of surface water pollution and the accumulation of pollutants along the course of the river. The paper presents the results of fluorimetric analysis of photosynthetic activity of natural phytoplankton cells and demonstrates the possibility of using fluorescence induction curves for regular monitoring measurements. Fluorescence parameters indicate a general deterioration of photosynthetic activity of natural phytoplankton. The growth of Oscillatoria agardhii in the waters of the Olkhovskoe Reservoir and of green microalgae in the Zuevskoe Reservoir led to an increase in the fluorescence quantum yield (Fv/Fm) and the total photosynthetic activity index (PI), which makes it possible to use these parameters as indicator parameters reflecting the intensity of “blooming” of various phytoplankton species.